Family support among patients with diabetic foot ulcer - Agus Miraj Darajat; Dede Nuraziz Muslim; Devi Defitri (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2024)
Background: Non-Communicable Diseases (NCDs) are a common cause of death in Indonesia, with Diabetes Mellitus (DM) being one of them. Diabetes Mellitus is a disease that occurs when the pancreas cannot produce insulin, or it is a chronic condition where the body cannot effectively use insulin, leading to increased blood glucose concentration or hyperglycemia, which is a characteristic of diabetes mellitus. The prevalence of diabetes mellitus has been increasing year by year, causing serious health issues in both developed and developing countries.Purpose: To identify the relationship between family support and injury incidents in patients with DM in the working area of the Cibiru Community Health Center, Bandung City in 2023.Method: This study is correlational in nature, utilizing a quantitative method conducted analytically and observationally, with cross-sectoral data collection. Chi-square analysis using Bivariate Test was employed, with a total of 40 respondents.Results: The mean age of the respondents was 59.5 with a standard deviation of 8.108 in the range of 45-75 years. The age group of 46-60 years constituted 55.5%, while the age group of 60-75 years was 45.0%. About 82.5% had high family support, 12.5% had moderate family support, and 5% had low family support. The bivariate analysis yielded a p-value of 0.027 when correlated with the occurrence of injuries. Thus, there is a relationship between family support and injury incidents in diabetic patients.Conclusion: Family support significantly influences the management or care of DM patients to minimize the occurrence of injuries.